Parental leave in European companies. Establishment survey on working time 2004-2005 - Anxo, Dominique; Fagan, Colette; Smith, Mark; Letablier, Marie-Thérèse; Perraudin, Corinne (Luxembourg, 2007)
"The Foundation’s Establishment Survey on Working Time and Work–Life Balance 2004–2005 set out to map the use of a variety of working time arrangements in companies, to assess the reasons for their introduction and their impact. This analytical report addresses the issue of parental leave as well as other forms of extended leave, such as leave to care for sick children or other adult family members. It offers a comparative review of the different national parental leave systems in operation, the differential use of parental leave by women and men across the 21 European countries and a discussion of the factors which influence take-up of parental leave by employees."